An Examination of Socio-Religious Practices of Sufi Adherents in Bida, Niger State - Yahaya, Abdulrahman (Teosofia: Indonesian Journal of Islamic Mysticism, 2023)
Sufis were known to have contributed to spreading Islam across the world. This paper seeks to encapsulate the early religious belief of the Nupe people in Bida, Niger state, until the introduction of Islam by the Sufis. The emergence of Sufism was assessed rightly from the time of Qadiriyyah Sufi practice and some scholars that were known with it, like Sheikh Abdulrahman Muhammad bin Sharif and Sheikh Muhammad Wazir (1882-1945), called “Waziri Mamma” before the emergence of Tijjaniyyah Sufi order through a scholar Man-Haruna, alias “Man-yisa Naku” in Banwuya, during the reign of the 2nd Etsu Nupe Muhammadu Saba (1859-1873) known as “Ma’asaba”. The paper adopted a qualitative survey where Interviews were conducted with seasoned Sufi members. The researchers purposively selected participants for the study because they are Muslims and possess knowledge about the phenomenon investigated. The paper provides an overview of some socio-religious practices of Sufis in Bida, Niger State, with the way and manner they are practised in accordance with the teachings of Islam and also reveals the effects of training on adherents by the Sufis in Bida.Contribution: This study contributes to revealing the shift of the Nupe people from polytheism to Monotheism with the role of the Sufis.